Molecular characterization of complement 9 in Epinephelus coioides and differential expression analysis of classical complement genes following Vibrio alginolyticus challenge - Luo, Sheng-Wei (Ecotoxicology (London, England), 2020)
Vibrio alginolyticus is posting an increasing threat to survival of grouper. Classical complement cascade can trigger initiation of immunity, while complement 9 (C9) is a major complement molecule involved in final step of membrane attack complex (MAC) formation. In this study, full-length EcC9 contained an ORF sequence of 1779 bp, encoding a polypeptide of 592 amino acids. A high-level expression of EcC9 mRNA was observed in liver. Following vibrio challenge, increased expression levels of EcC1q, EcBf/C2, EcC4, EcC6, EcC7 and EcC9 mRNA were detected in liver and kidney. These results implied that elevated expression level of classical complement pathway (CCP) and terminal complement components (TCCs) may assess toxicological effect of V. alginolyticus